1998
DOI: 10.1093/ije/27.6.1000
|View full text |Cite
|
Sign up to set email alerts
|

Health status of Persian Gulf War veterans: self-reported symptoms, environmental exposures and the effect of stress

Abstract: Veterans deployed to the Persian Gulf have higher self-reported prevalence of health symptoms compared to PGW veterans who were deployed only as far as Germany. Several Gulf-service environmental exposures are associated with increased health symptom reporting involving predicted body-systems, after adjusting for war-zone stressor exposures and PTSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
151
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(158 citation statements)
references
References 6 publications
4
151
0
2
Order By: Relevance
“…In fact, a range of other exposures show associations in many studies as well, although these are commonly weaker and/or less consistent. Moreover, compared with AChEi exposures and the broader exposure classes (e.g., pesticides) queried to get at them, the relation of other exposures to multisymptom illness is less consistently retained (perhaps excepting anthrax and multiple vaccines) or is consistently lost (e.g., psychological stressors) in models that adjust for other exposures (17,24,25,30,33,35).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, a range of other exposures show associations in many studies as well, although these are commonly weaker and/or less consistent. Moreover, compared with AChEi exposures and the broader exposure classes (e.g., pesticides) queried to get at them, the relation of other exposures to multisymptom illness is less consistently retained (perhaps excepting anthrax and multiple vaccines) or is consistently lost (e.g., psychological stressors) in models that adjust for other exposures (17,24,25,30,33,35).…”
Section: Resultsmentioning
confidence: 99%
“…Gulf War veterans have reported multiple chronic symptoms, and multiple studies have found a higher prevalence of symptoms among Gulf War veterans compared with military controls [4][5][6][7][8][9]. Data from several large, populationbased studies with appropriate controls demonstrate that the pattern of symptoms is comparable in Gulf War deployed and Gulf War era personnel [6,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Gulf War veterans have reported a higher prevalence of symptoms than contemporaneous soldiers not deployed to the war for many illnesses, including bronchitis and asthma (2)(3)(4)(5)(6)(7)(8)(9)(10). Principal respiratory exposures that occurred during the war include combustion products, chemical agent-resistant coating paint, sand, and smoke emanating from oilwell fires within Kuwait.…”
mentioning
confidence: 99%